2021
DOI: 10.1097/dss.0000000000003280
|View full text |Cite
|
Sign up to set email alerts
|

Immunostained Frozen Sections Vs Traditional Permanent Paraffin Sections for Lentigo Maligna Treated With Mohs Micrographic Surgery

Abstract: BACKGROUND Mohs micrographic surgery (MMS) has risen in popularity as a management option for treating lentigo maligna (LM) because of its ability to accurately detect subclinical spread while conserving tissue. The primary concern for opponents of MMS in melanoma remains the difficulty associated with interpretation of frozen sections compared with traditional paraffin sections; this has been made easier with the advent of immunostaining. OBJECTIVE Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Nonetheless, the use of immunostained frozen sections does not fully negate the risk of overtreatment of melanocytic hyperplasia using en face sectioning, compared with conventional vertical cross sections towards the tissue edge 76 . This issue is further highlighted in the study by Punchihewa et al 9 where there was a 13% disagreement compared with traditional permanent paraffin‐embedded sections for LM treated by MMS. Finally, the follow‐up period of classic MMS, slow‐MMS, and to a lesser extent SE with complete margin assessment, was limited or in some studies not reported on.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the use of immunostained frozen sections does not fully negate the risk of overtreatment of melanocytic hyperplasia using en face sectioning, compared with conventional vertical cross sections towards the tissue edge 76 . This issue is further highlighted in the study by Punchihewa et al 9 where there was a 13% disagreement compared with traditional permanent paraffin‐embedded sections for LM treated by MMS. Finally, the follow‐up period of classic MMS, slow‐MMS, and to a lesser extent SE with complete margin assessment, was limited or in some studies not reported on.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, MMS is not only limited by requiring extensive training, but more importantly, the use of frozen sections is not universally accepted in the treatment of melanocytic lesions as it can result in artefactual and fixational changes in the excisional specimens. 9 To circumvent this issue (rushed) permanent paraffin-embedded sections (i.e. 'Slow' Mohs) or frozen sections with immunohistochemistry (IHC) staining are increasingly being used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation